2017
DOI: 10.1088/1361-6455/aa7f01
|View full text |Cite
|
Sign up to set email alerts
|

Classical hallmarks of macroscopic quantum wave function propagation

Abstract: The precise connection between quantum wave functions and the underlying classical trajectories often is presented rather vaguely by practitioners of quantum mechanics. Here we demonstrate, with simple examples, that the imaging theorem (IT) based on the semiclassical propagator provides a precise connection. Wave functions are preserved out to macroscopic distances but the variables, position and momentum of these functions describe classical trajectories. We show that the IT, based on an overtly time-depende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In Ref. 5–7, it is shown that the IT remains valid for typical weak particle‐extraction fields and where more than one trajectory contributes to the final wave function at fixed r$\bm{r}$ and t$t$. For the simple case of completely free propagation of interest here, the IT is valid in the far zone of wave propagation in complete analogy to the transition to beam optics in light wave propagation.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…In Ref. 5–7, it is shown that the IT remains valid for typical weak particle‐extraction fields and where more than one trajectory contributes to the final wave function at fixed r$\bm{r}$ and t$t$. For the simple case of completely free propagation of interest here, the IT is valid in the far zone of wave propagation in complete analogy to the transition to beam optics in light wave propagation.…”
Section: Introductionmentioning
confidence: 93%
“…This equation is known as the IT approximation for the final wavefunction normalΨfalse(bold-italicr,tfalse)$\Psi (\bm{r}, t)$ 5–7 . Actually, suitably generalised, it is valid for motion in arbitrarily applied fields and where more than one trajectory contributes to the final wave function 5–7 .…”
Section: Wave Function Propagation In Space and Timementioning
confidence: 99%
See 3 more Smart Citations